Adult Head and Neck Soft Tissue Sarcomas: Treatment and Outcome. (26th February 2008) - Singh, Rabindra P.; Grimer, Robert J.; Bhujel, Nabina; Carter, Simon R.; Tillman, Roger M.; Abudu, Adesegun
Abstract : We have retrospectively analysed the experience of a musculoskeletal oncological unit in the management of adult head and neck soft tissue sarcomas from 1990 to 2005. Thirty-six patients were seen, of whom 24 were treated at this unit, the remainder only receiving advice. The median age of the patients was 46 years. Most of the sarcomas were deep and of high or intermediate grade with a median size of 5.5 cm. Eleven different histological subtypes were identified. Wide excision was possible only in 21% of the cases. 42% of the patients developed local recurrence and 42% developed metastatic disease usually in the lungs. Overall survival was 49% at 5 years. Tumour size was the most important prognostic factor. Adult head and neck soft tissue sarcomas have a high mortality rate with a high risk of local recurrence and metastatic disease. The rarity of the disease would suggest that centralisation of care could lead to increased expertise and better outcomes.